THE EFFECT OF ISLAMIC RELIGIOUS EDUCATION TEACHERS TO LEARNING STUDENTS’ SPIRIT AT ENREKANG JUNIOR HIGH SCHOOL - Rizqy Mutmainnah Amin; Erwin Hafid; Baharuddin Baharuddin (JICSA : Journal of Islamic Civilization in Southeast Asian, 2021)
The objectives of this study are to describe the leadership of Islamic Religious Education teachers in class VIII of Junior High School (SMPN) 1 Enrekang. It also describe the motivation of students in class VIII SMPN 1 Enrekang. The paper also describe the learning interest of students in class VIII of SMPN 1 Enrekang as well as testing the influence of Islamic Religious Education teacher leadership on the motivation of students in class VIII of SMPN 1 Enrekang. Besides, the research also test the influence of Islamic Religious Education teacher leadership on students' learning interest in class VIII of SMPN 1 Enrekang. Furthermore, it test the influence of Islamic Religious Education teacher leadership on students' motivation and interest in learning in class VIII of SMPN 1 Enrekang. Thus, there is an influence of the leadership of Islamic Religious Education teachers on the learning interest of students in class VIII of SMPN 1 Enrekang.